Analisis Faktor Penyebab Rendahnya Kemampuan Literasi Membaca Siswa Kelas V SDN 1 Suntalangu - Ihwan Ihwan; Nyoman Dantes; Desak Putu Parmiti (LPPM Institut Pendidikan Nusantara Global, 2026)
The results of the study show that. The first test showed that the average reading ability of students was in the sufficient category, with an average score of 67.75%. The category distribution showed that most students (68.75%) were in the adequate category, while only 12.5% of students were in the very good category. These findings indicate that there are general difficulties among students in understanding the content of the reading, summarizing information, and reexpressing the content of the story in a sequential manner. However, after a more targeted learning intervention, the second test showed a significant improvement with the average score increasing to 78.44%. The number of students in the very good category increased to 37.5%, and those in the good category reached 31.25%. These results show that students have literacy potential that can be developed more optimally with the right support. From the results of the interview, it is known that there are two main factors that affect students' low reading literacy skills, namely internal factors (low reading interest, lack of motivation to learn, and limitations in reading comprehension), as well as external factors (limited supporting facilities and infrastructure, lack of interesting reading materials, and lack of parental involvement). These findings confirm the importance of the role of schools and families in creating an environment that supports the growth of literacy culture.